2020
DOI: 10.1530/eje-19-0968
|View full text |Cite
|
Sign up to set email alerts
|

Performance of deep neural network-based artificial intelligence method in diabetic retinopathy screening: a systematic review and meta-analysis of diagnostic test accuracy

Abstract: Objective Automatic diabetic retinopathy screening system based on neural networks has been used to detect diabetic retinopathy (DR). However, there is no quantitative synthesis of performance of these methods. We aimed to estimate the sensitivity and specificity of neural networks in DR grading. Methods Medline, Embase, IEEE Xplore, and Cochrane Library were searched up to 23 July 2019. Studies that evaluated performance of neural networks in detection of moderate or worse DR or diabetic macular edema using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Representative and high-quality studies focused on different diseases using various known AI methods and were conducted in different countries. Our study summarized and quantitatively analyzed heterogeneous studies on the automatic diagnosis of different diseases based on facial features, showing a pooled sensitivity of 89% (95% CI 82% to 93%) and a specificity of 92% (95% CI 87% to 95%), similar to the results of previous meta-analyses on automatic image recognition for diabetic retinopathy screening [8,33,34], colorectal neoplasia, and breast cancer [35][36][37][38], indicating a promising diagnostic performance of facial recognition based on AI for heterogeneous diseases. A sensitivity analysis was conducted to evaluate the robustness of the results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Representative and high-quality studies focused on different diseases using various known AI methods and were conducted in different countries. Our study summarized and quantitatively analyzed heterogeneous studies on the automatic diagnosis of different diseases based on facial features, showing a pooled sensitivity of 89% (95% CI 82% to 93%) and a specificity of 92% (95% CI 87% to 95%), similar to the results of previous meta-analyses on automatic image recognition for diabetic retinopathy screening [8,33,34], colorectal neoplasia, and breast cancer [35][36][37][38], indicating a promising diagnostic performance of facial recognition based on AI for heterogeneous diseases. A sensitivity analysis was conducted to evaluate the robustness of the results.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have demonstrated that the image characteristics of diseases play an important role in the performance of image recognition by AI methods [43], including the automatic screening of pulmonary nodules [7,44,45], referable glaucomatous optic neuropathy (GON) [46], colorectal adenoma and polyps [47,48], which also indicates that IRI describes image characteristics of diseases and is critical for AI performance in automatic image recognition. As has been shown before for diabetic retinopathy screening, no statistically significant contribution to heterogeneous diagnostic accuracy has been demonstrated for sample size of the training sets and architecture of convolutional neural networks [34]. Therefore, the complexity theory explains the relationship between complexity of a disease and AI performance and should be extended to other AI applications.…”
Section: Discussionmentioning
confidence: 83%
“…Our study results are only applicable to teleretinal programmes using human graders. Recent diagnostic test accuracy meta-analyses have provided very promising accuracy estimates for machine-learning-based teleretinal screening programmes for DR. 38 39 Future studies should assess the diagnostic accuracy of automated systems using artificial intelligence and deep-learning algorithms in teleophthalmology screening programmes for ocular diseases. 40 Lastly, the focus of this review was on teleretinal screening for the most common retinal pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…In the short-to medium-period, the clinical management of geriatric DM can be improved by initiating multidisciplinary, multi-specialist care networks, in which ophthalmologists and orthoptist/ophthalmic assistant are involved to develop: i) tele-medicine procedures for the screening of diabetic retinopathy and other diabetes-related eye disorders using either conventional or innovative AI-based approaches [37][38][39] ; ii) algorithms for personalized treatments of diabetic macular edema as well as other eye disorders frequently present in geriatric DM patients, analyzing their outcomes also using AI-equipped systems [40][41][42] ; iii) multidisciplinary rehabilitation programs that can meet the needs of the visually impaired DM persons among geriatric population [43][44][45][46] .…”
Section: Appendixmentioning
confidence: 99%